Accelerometry-Derived Relative Exercise Intensities in Elite Women’s Basketball - Staunton, Craig; Wundersitz, Daniel; Gordon, Brett; Kingsley, Michael (International Journal of Sports Medicine, 2018)
This study assessed accelerometry-derived relative exercise intensity during elite women’s basketball match play. The influence of player position/role and match period on relative exercise intensities was evaluated. Ten basketballers wore accelerometers during a Yo-Yo intermittent recovery test (Yo-Yo-IR1) and 18 competitive matches. Relative exercise intensity was quantified using predicted oxygen consumption reserve determined using correlations from Yo-Yo-IR1. Total time, bout frequency and bout duration were calculated in seven intensity zones and compared between quarters, positions (back-court vs. front-court) and roles (starters vs. bench). Back-court players spent 6.0±1.9% more match time performing supramaximal activity when compared to front-court players (p<0.045). Back-court players experienced more supramaximal bouts (125±37 vs. 52±36; p=0.031) of greater average duration (2.1±0.4 vs. 1.4±0.2 s; p=0.021) and maximum duration (7±2 vs. 3±1 s; p=0.020). More sedentary to very light activity was observed in the 2nd and 4th quarters compared to the 1st and 3rd quarters (p<0.05). Despite reduced playing time, bench players performed similar amounts of maximal and supramaximal exercise when compared to starters (p≥0.279). Player position, role and match periods influence the demands of women’s basketball; these factors should be considered when designing match-specific conditioning programs.
Keywords: female; training load; monitoring; accelerometer; workloads